Ethnomedicinal minerals and geological materials used by traditional Iranian Turkic healers - Eslam Mostafavi Maresht (World Scientific Publishing, 2024)
Ethnic knowledge and traditional medicine of the Iranian Turkic people are a significant source of ancient wisdom and treatments for various diseases based on natural resources. This study aimed to preserve their cultural heritage, to act as a foundation for developing contemporary pharmaceuticals and to promote sustainable development. Moreover, these medications are very natural, inexpensive, low-risk, and have few adverse effects. Twelve highly experienced and influential traditional healers from twelve villages were studied. The research was conducted in Azerbaijani Turkish from March to May 2019 using purposive sampling and semi-structured interviews. The interviews included training, maladies treated, treatment techniques, preparation methods, and drug administration methods. Additionally, multiple treatment sessions were observed. A field study was also carried out to identify and document the location of, and process for accessing, minerals around the villages. The results were analyzed using the quantitative informant consensus factor and Use Value (UV) indices. A total of 22 distinct categories of mineral elements and nine main disease categories treated with these elements were identified. Kerosene had the highest consumption value ([Formula: see text]) and was the most significant and extensively utilized medicinal mineral. All consensus values were higher than 0.84, indicating high consensus among therapists regarding the treatment of diseases in these areas. Topical applications dominated, and the category of skin diseases had the highest percentage of treatments with medicinal minerals.